Beyond self-serving bias: diffusion of responsibility reduces sense of agency and outcome monitoring. Issue 1 (1st December 2016) - Beyer, Frederike; Sidarus, Nura; Bonicalzi, Sofia; Haggard, Patrick
Abstract: Diffusion of responsibility across agents has been proposed to underlie decreased helping and increased aggression in group behaviour. However, few studies have directly investigated effects of the presence of other people on how we experience the consequences of our actions. This EEG study investigated whether diffusion of responsibility simply reflects a post-hoc self-serving bias, or rather has direct effects on how we process the outcomes of our actions, and our experience of agency over them. Participants made voluntary actions whose outcomes were more or less negative. Presence of another potential agent reduced participants' sense of agency over those outcomes, even though it was always obvious who caused each outcome. Further, presence of another agent reduced the amplitude of feedback-related negativity evoked by outcome stimuli, suggesting reduced outcome monitoring. The presence of other agents may lead to diffusion of responsibility by weakening the neural linkage between one's actions and their outcomes.